If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 16x + -16 = 12x + -6 Reorder the terms: 10 + -16 + 16x = 12x + -6 Combine like terms: 10 + -16 = -6 -6 + 16x = 12x + -6 Reorder the terms: -6 + 16x = -6 + 12x Add '6' to each side of the equation. -6 + 6 + 16x = -6 + 6 + 12x Combine like terms: -6 + 6 = 0 0 + 16x = -6 + 6 + 12x 16x = -6 + 6 + 12x Combine like terms: -6 + 6 = 0 16x = 0 + 12x 16x = 12x Solving 16x = 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 16x + -12x = 12x + -12x Combine like terms: 16x + -12x = 4x 4x = 12x + -12x Combine like terms: 12x + -12x = 0 4x = 0 Divide each side by '4'. x = 0 Simplifying x = 0
| -3(-2)+7= | | 5(x+3)/3=4x-2 | | -89=-3(4+3p)-5 | | -5(-2)+9= | | (243)^(3/5) | | 15x-9=7+6-2x | | 243^3/5 | | -5(-1)+9(-1)= | | 50+15x=25x | | -3+2n=n+3 | | 49=-6x+2x+1 | | 5c-4c=c+20 | | -3.5-(-6.6)= | | -5(-2)+9(-2)= | | 7h/h | | 7x^2+9x-3x^4+6=0 | | 9h^2/h | | xc^2-8=a^2+5x | | 25x=15x | | 1-6z=-71 | | 15=9+t | | 8x^3y^2+7xy-4x^4y^3=0 | | 73-18+8w=67 | | x/(1-x)=28/38 | | 2(2x-1)+2(x+2)=(x+7)+(2x+5)+(2x+7) | | x/(1-x)=28/18 | | x/(1-x)=38/28 | | ((2)/(x-3))-(1)/(x-1) | | 7(6a+7)=-203 | | 36=-4/9c | | x/(1-x)=18/28 | | 5(t-5)+7t=4(3t+3)-8 |